Sacred Authority and Silent Violence: Theological Capital and the Symbolic Production of Sexual Abuse in Pesantren - Riyadi, Sugeng (The Sociology of Islam, 2026)
This article examines how religious authority operates through symbolic mechanisms to produce and sustain the subordination of female students in an Indonesian pesantren (Islamic boarding school). Drawing on Pierre Bourdieu’s concepts of field, habitus, symbolic capital, symbolic power, symbolic violence, doxa, and misrecognition, the study investigates a case of sexual violence involving female students in a pesantren in East Java. Employing a qualitative case study approach, data were collected through in-depth interviews with victims, victim advocates, and pesantren administrators, supported by documentary sources. The findings reveal that the kyai’s religious legitimacy functions as symbolic capital that generates obedience through the culture of ta'dzim, reverence for religious authority, and the pursuit of blessed knowledge. These dispositions are internalized as a patriarchal habitus that normalizes unequal gender relations and limits victims’ capacity to resist or report abuse. The study argues that sexual violence in pesantren should be understood not merely as individual misconduct but as a manifestation of symbolic domination embedded within religious authority and patriarchal social structures.